Comparative study of preimplantation development following distinct assisted oocyte activation protocols in a PLC-zeta knockout mouse model. (8th September 2020) - Ferrer-Buitrago, M; Tilleman, L; Thys, V; Hachem, A; Boel, A; Van Nieuwerburgh, F; Deforce, D; Leybaert, L; De Sutter, P; Parrington, J; Heindryckx, B
Abstract: Mammalian fertilization encompasses a series of Ca 2+ oscillations initiated by the sperm factor phospholipase C zeta (PLCζ). Some studies have shown that altering the Ca 2+ oscillatory regime at fertilization affects preimplantation blastocyst development. However, assisted oocyte activation (AOA) protocols can induce oocyte activation in a manner that diverges profoundly from the physiological Ca 2+ profiling. In our study, we used the newly developed PLCζ-null sperm to investigate the independent effect of AOA on mouse preimplantation embryogenesis. Based on previous findings, we hypothesized that AOA protocols with Ca 2+ oscillatory responses might improve blastocyst formation rates and differing Ca 2+ profiles might alter blastocyst transcriptomes. A total of 326 MII B6D2F1-oocytes were used to describe Ca 2+ profiles and to compare embryonic development and individual blastocyst transcriptomes between four control conditions: C1 ( in-vivo fertilization), C2 (ICSI control sperm), C3 (parthenogenesis) and C4 (ICSI-PLCζ-KO sperm) and four AOA groups: AOA1 (human recombinant PLCζ), AOA2 (Sr 2+ ), AOA3 (ionomycin) and AOA4 (TPEN). All groups revealed remarkable variations in their Ca 2+ profiles; however, oocyte activation rates were comparable between the controls (91.1% ± 13.8%) and AOA (86.9% ± 11.1%) groups. AOA methods which enable Ca 2+ oscillatory responses (AOA1: 41% and AOA2: 75%) or single Ca 2+ transients (AOA3: 50%) showed no significantly different blastocyst rates compared to ICSI control group (C2: 70%). In contrast, we observed a significant decrease in compaction (53% vs. 83%) and blastocyst rates (41% vs. 70%) in the absence of an initial Ca 2+ trigger (AOA4) compared with the C2 group. Transcription profiles did not identify significant differences in gene expression levels between the ICSI control group (C2) and the four AOA groups.